IMPLEMENTASI PRINSIP RESTORATIVE JUSTICE TERHADAP PELAKU PENYALAHGUNAAN NARKOTIKA DI KEJAKSAAN NEGERI PONTIANAK - NIM. A1011201144, MAYANG SEPTYFEBIOLA (Jurnal Fatwa Hukum, 2024)
AbstractRestorative justice has emerged as a new alternative for resolving drug abuse cases at the Prosecutor's Office since the implementation of the Attorney General's Guideline Number 18 of 2021. The research problem addressed in this thesis focuses on the challenges in implementing restorative justice for drug abuse offenders at the Pontianak District Prosecutor's Office. The research problem explored in this thesis is the challenges in implementing restorative justice for drug abuse offenders at the Pontianak District Prosecutor's Office. This study is classified as Empirical Juridical Research. The research uses primary data obtained through field studies, such as observations and direct interviews, while secondary data is sourced from literature reviews, legal materials, and supporting legal documents. The theories applied in this research include the theory of legal certainty and John Rawls' theory of justice. Restorative justice emphasizes restoration and the prevailing legal utility values, allowing drug abuse offenders who meet certain criteria the opportunity to undergo rehabilitation. Considering that the Pontianak District Prosecutor's Office has not implemented restorative justice in drug abuse cases since the enactment of the relevant legal regulations up to the time this research was conducted, the main finding of this study indicates that the obstacles to the implementation of restorative justice for drug abuse offenders are primarily due to inhibiting factors outweighing supporting factors. The inhibiting factors include differences in perspectives among law enforcement officials, particularly prosecutors who control the case during the prosecution stage, the limited resources of facilities and rehabilitation centers, and the lack of cooperation between authorized agencies and the Integrated Assessment Team (TAT), which plays a crucial role in the rehabilitation process. The classification of someone as an abuser cannot be determined independently by the Prosecutor but must be proven through an Integrated Assessment by the TAT.      Keywords: Restorative justice, Drug Abuse  AbstrakRestorative justice menjadi alternatif baru dalam penyelesaian perkara penyalahgunaan narkotika di Kejaksaan terhitung sejak disahkannya Pedoman Jaksa Agung Nomor 18 Tahun 2021. Rumusan masalah yang dikaji dalam penelitian skripsi ini adalah kendala penerapan Restorative justice terhadap pelaku penyalahgunaan narkotika di Kejaksaan Negeri Pontianak. Jenis penelitian ini merupakan penelitian Yuridis Empiris. Penelitian menggunakan data primer yang diperoleh melalui studi lapangan baik itu observasi dan wawancara langsung sedangkan data sekunder diperoleh dari studi kepustakaan, bahan-bahan hukum serta dokumen hukum sebagai penunjang.Teori yang digunakan merupakan teori kepastian hukum dan teori keadilan berdasarkan pandangan John Rawls. Restorative justice menekankan pemulihan pada keadaan semula dan nilai-nilai kemanfaatan hukum yang berlaku sehingga pelaku penyalahgunaan narkotika yang memenuhi syarat mendapatkan kesempatan menjalani rehabilitasi. Mengingat Kejaksaan Negeri Pontianak belum menerapkan restorative justice pada perkara penyalahgunaan narkotika terhitung sejak disahkannya regulasi hukum yang mengatur sampai pada saat penelitian ini dilakukan maka, temuan utama penelitian ini menunjukan bahwa kendala penerapan restorative justice pada pelaku penyalahgunaan narkotika disebabkan faktor penghambat lebih besar dari faktor pendukung. Faktor penghambat yaitu perbedaan pandangan antar aparat penegak hukum khususnya Jaksa sebagai pemilik perkara pada tahap penuntutan, minimnya sumber daya fasilitas dan balai rehabilitasi serta kurangnya kerjasama antar instansi yang berwenang bersama Tim Asesmen Terpadu yang berperan penting dalam proses pelaksanaan rehabilitasi sebab pembuktian seorang di kualifikasikan penyalahguna tidak dapat dilakukan oleh Jaksa secara mandiri melainkan hanya dapat dibuktikan melalui Asesmen Terpadu oleh Tim Asesmen Terpadu (TAT).  Kata Kunci : Restorative justice. Penyalahgunaan Narkotika